Prevalence of non-communicable disease risk factors among nurses and para-health professionals working at primary healthcare level of Bangladesh: a cross-sectional study - Palash Chandra Banik; Lingkan Barua; Liaquat Ali; Mithila Faruque; Sharmin Sultana; Animesh Biswas; Abdul Alim; Pradip Kumar Sen Gupta (BMJ Open)
Objective To determine the prevalence of non-communicable disease (NCD) risk factors among nurses and para-health professionals (PHPs) working at primary healthcare centres in Bangladesh. In addition to this, we also investigated the association of these risk factors with the categories of health professions.Design Cross-sectional study and the sampling technique was a census.Setting The study site was a medical university of Bangladesh where the study population was recruited by NCD Control Programme of Directorate General of Health Services to participate in a 3-day training session from November 2017 to May 2018.Participants A total of 1942 government-employed senior staff nurses (SSNs) and PHPs working at Upazila Health Complexes.Primary and secondary outcome measures The data were collected using a modified STEPwise approach to NCD risk factors surveillance questionnaire of the World Health Organisation (V.3.2). The prevalence of NCD risk factors was presented descriptively and the χ² test was used to determine the association between NCD risk factors distribution and categories of health professions.Results The mean age of the participants was 37.6 years (SD 9.5) and most of them (87.6%) had a diploma in their respective fields. Physical inactivity (86.9%), inadequate fruits and/vegetable intake (56.3%) and added salt intake (35.6%) were the most prevalent behavioural risk factors. The prevalence of central obesity, overweight, raised blood glucose and raised BP were 83.5%, 42.6%, 19.2% and 12.8% respectively. Overall, the NCD risk factors prevalence was higher among PHPs compared with SSNs. A highly significant association (p<0.001) was found between risk factors and the categories of health professions for tobacco use, alcohol intake, added salt intake and physical inactivity.Conclusion High NCD risk factors prevalence and its significant association with SSNs and PHPs demand an appropriate risk-reduction strategy to minimise the possibility of chronic illness among them.